Awareness of primary spontaneous hemorrhagic angiosarcoma of the breast associated with Kasabach–Merritt syndrome in a pregnant woman by enhanced magnetic resonance imaging: A CARE-compliant case report. Issue 44 (November 2016) - Lin, Wei-Ming; Juan, Yu-Hsiang; Lin, Yu-Ching; Ueng, Shir-Hwa; Lo, Yung-Feng; Cheung, Yun-Chung
Abstract: Introduction: Primary breast angiosarcoma with spontaneous intratumoral bleeding associating with Kasabach-Merritt Syndrome is rarely reported. Case Findings/Patient Concerns: We herein present such a case in a 30-year-old pregnant woman who was initially diagnosed to hemangioma at her early gestation. However, the sudden rapid tumor growth was aware of the attention and intended for receiving the breast enhanced magnetic resonance imaging. Diagnoses and Interventions: The dynamic MRI enhancement showed inhomogenous enhancement at the periphery of the lobulated tumor on both early and delayed scans, otherwise a large hematoma was revealed at the center. Surgical resection was performed after baby delivery by Caeserean section, and histopathologic study confirmed breast angiosarcoma. Conclusion: Despite its rarity, clinicians should recognize the association of breast angiosacroma with Kasabach-Merritt Syndrome with suggestive finding of enhanced MRI in order to decide the surgical approach.